Importance of a distal proximal contact on load transfer by implant-supported single adjacent crowns in posterior region of the mandible: a photoelastic study - Fabio Afranio de Aguiar Junior; Rodrigo Tiossi; Ana Paula Macedo; Maria da Gloria Chiarello de Mattos; Ricardo Faria Ribeiro; Renata Cristina Silveira Rodrigues (University of São Paulo, 2013)
OBJECTIVE: This study aimed to evaluate the importance of a distal proximal contact on the load transfer to the posterior region of the mandible by non-splinted adjacent implant-supported crowns using photoelastic stress analysis. MATERIAL AND METHODS: A rectangular model (68x30x15 mm) was made of polymethylmethacrylate resin to simulate half of the mandibular arch. One model was completed with resin replicas representing the first premolar and second molar and with two 3.75 mm dia.x11 mm internal hexagon threaded implants replacing the second premolar and first molar. The other model was manufactured in the same way but without the second molar. Both models were duplicated using photoelastic resin. The roots of the teeth replicas were covered with a layer of polyether impression material to simulate the periodontal ligament. Two different vertical loads were applied to the crowns as follows: 1 - single static point load alternately applied to the crowns replacing the second premolar and first molar (50 N); 2 - simultaneous static point loads applied to both of the crowns replacing the second premolar and first molar (100 N). The resulting isochromatic fringe pattern in the photoelastic model was monitored and photographed. RESULTS: All loading conditions studied showed that the presence of the second molar has changed the load transmission and the pattern of stresses. CONCLUSION: Results showed that the presence of a second molar proximal contact can help minimize the stresses around the implants.